Accuracy of Ultrasonography in Predicting Factors That Make Laparoscopic Cholecystectomy Difficult - Muhammad Raheem; Sajid Ali Shah; S H Waqar (Aziz Fatimah Medical and Dental College, 2022)
Objective: To determine the accuracy of ultrasound in predicting difficult laproscopic cholecystectomy,keeping preoperative findings as gold standard. Methodology: A cross sectional study was conducted from July 2018 to January 2019 at Pakistan Institute of Medical Sciences Islamabad. Adult patients wih cholelithiasis were included in the study by consecutive sampling, who underwent laproscopic cholecystectomy. Preoperative ultrasound parameters such as gallbladder wall thickness, size and number of gall stones, contracted gall bladder and pericholecystic fluid were studied. Intraoperative difficulty of laproscopic cholecystectomy was determined by criteria as procedure time more than 60 minutes, dissection at Calot's triangle more than 30 minutes and tear of gall bladder  Results: A total of 150 patients were included with mean age of 41.4 ± 9.9 years . There were 29 (19.3%) males and 121 (80.7%) were female. Male to Female ratio was 1:4, preoperative ultrasonography findings such as gallbladder wall thickness > 4mm ,size of stone >1cm impacted gall stone , contracted gallbladder and presence of pericholicystic fluid were significantly associated with difficult laproscopic cholycytectomy (p value=0.001) Conclusion: In majority of patients, preoperative ultrasonography is found as good predictor of difficult laproscopic cholycystectomy and should be used as a screening procedures.